Devir urbano, direito à cidade e políticas públicas: urbanidade e espacialidades em Curitiba - Pilarski, Mariel Mayer (2020)
The right to the city with the advent of the 1988 Federal Constitution changes to another category and special attention must be given to the urban planning of our municipalities, só that, in fact, what is proposed constitutionally, striving for a healthy, harmonious and integrated environment. This dissertation means to analyze how the spatial elements interfere, in Curitiba city, for the realization of the right to the city and the consequent ontological dimension of urbanities that characterize it. To achieve that, whore made categories from the theoretical discussion put by Ascher, Netto, Surel, Kuhn, Lefebvre, Capra and Milton Santos about the urban, urbanities, public policies and paradigm shifts. The general objective of this dissertation is to analyze how, in the mentioned city, spatial elements interfere for the realization of the right to the city and the consequent ontological dimension of urbanities that characterize it, based on the theorists used, for the proper categorization. The specific objectives are: to carry out a bibliographic review on urbanities, urban planning and the right to the city; establish the spatial dimensions of urbanities in Curitiba, within the object of study of this work, based on Netto’s theory; carry out a case study of how the spatial elements in Curitiba interfere in the realization of the dimensions of urbanities and; make suggestions só that the municipality of Curitiba can have urban planning tools. The methodology as to approach will be qualitative; how much nature is applied; the objectives are exploratory, descriptive, and explanatory and the procedures are: documentary, bibliographic and case study. After the separation that was proposed in the methodology, maps (to have a spatial notion of where the equipment is located) and tables were elaborated. From the analysis of each municipal public equipment, comparing the amount with the per capita income and the number of inhabitants by regional, there was a separation in total / partially integrated, distant, or excluded from urbanity. The tendency that this dissertation has concluded is that, despite the large amount of equipment available, currently the expectations of what is essential for integrated urbanity – and effective right to the city, especially with regard to distribution of equipment by the number of people living in the appropriate locations.